The effectiveness nitrogen balance urea cotton using nitrification inhibitor washed typical sierozems - Khashimov F.Kh.; Tashkenbaev O.N.; Umurzakov A.A. (BIO Web of Conferences)
In the conditions of the sierozem zone soils, where the nitrogen content is relatively low, nitrogen fertilizers play the leading role among the fertilizers used for cotton. Nitrogen losses due to washout, denitrification, etc., during the growing season can reach 50% or more, and therefore the study of the effect of the nitrification inhibitor KMP on the efficiency of nitrogen fertilizers and the nitrogen balance using the nitrogen isotope 15N when applying urea for cotton is of great importance. Small-plot and field experiments with cotton were carried out on irrigation-eroded washed-out typical sierozem and were laid in the upper part of the slopes of the massifs. Nitrogen was applied against the background of RK in the form of urea enriched with 15N - 23-25%. The use of nitrification inhibitors with urea and slow-release fertilizers increased the use of fertilizer nitrogen to 38.1%, fixation of fertilizer nitrogen in the soil from 21.4 to 29.3%, reduced nitrogen losses with waste water and as a result of washout from 10.3 to 4.5%. Losses of fertilizer nitrogen due to washout and volatilization decreased from 35.8 to 19.6%.